If 7 \cosec( \alpha ) - 3 \cot( \alpha ) = 77cosec(α)−3cot(α)=7
then prove that
7 \cot( \alpha ) - 3 \cosec( \alpha ) = 37cot(α)−3cosec(α)=3
Please solve the qûēßtìøñ
![](https://hi-static.z-dn.net/files/d09/bbe0158cdb4239354516a4520fa9ebb7.jpg)
Answers
Given---> 7 Cosecθ - 3 Cotθ = 7
To prove---> 7 Cotθ - 3 Cosecθ = 3
Proof ---> ATQ,
7 Cosecθ - 3 Cotθ = 7
=> 7 Cosecθ - 7 = 3 Cotθ
=> 7 ( Cosecθ - 1 ) = 3 Cotθ
Multiplying both sides by ( Cosecθ - 1 )
=> 7(Cosecθ - 1) (Cosecθ + 1) = 3 Cotθ(Cosecθ+ 1 )
We have an identiy , a² - b² = ( a + b ) ( a - b ) , applying it in LHS, we get,
=> 7 { ( Cosec²θ - ( 1 )² } = 3 Cotθ ( Cosecθ + 1 )
=> 7 ( Cosec²θ - 1 ) = 3 Cotθ ( Cosecθ + 1 )
We know that , Cosec²A - 1 = Cot²A , applying it in LHS , we get,
=> 7 Cot²θ = 3 Cotθ ( Cosecθ + 1 )
Cotθ is cancel out from both sides and we get,
=> 7 Cotθ = 3 ( Cosecθ + 1 )
=> 7 Cotθ = 3 Cosecθ + 3
=> 7 Cotθ - 3 Cosecθ = 3
Hence Proved
Answer:
Answer in attachment.
Mark me as brainliest plzz
![](https://hi-static.z-dn.net/files/d12/c1b1d2aadb180289e36e73745b571272.jpg)
![](https://hi-static.z-dn.net/files/dc6/3e8c427eee2d762fbf41ad71d29c1d31.jpg)
![](https://hi-static.z-dn.net/files/de4/419ecf517e3d640094e6b0e067d5da33.jpg)